Impact of early PCSK9 inhibitor treatment on heart after percutaneous coronary intervention in patients with STEMI: Design and rationale of the PERFECT II trial - Xia, Jiachun; Wang, Xinyue; Zhou, Jun; Wang, Dong; Pang, Yanan; Xu, Xin; Sang, Zhenchi; Zhang, Yi; Zhang, Junfeng; Wu, Sicheng; Xiao, Zhengguang; Hou, Lei (Frontiers in Cardiovascular Medicine, 2022)
Background and aims: Primary percutaneous coronary intervention (PPCI) is the most effective treatment strategy for ST-segment elevation myocardial infarction (STEMI). Nevertheless, dysregulated inflammation induced by myocardial reperfusion injury may increase the final infarct size and induce maladaptive myocardial remodeling. Proprotein convertase subtilisin/kexin 9 (PCSK9) inhibitor, as a novel and potent lipid-lowering drug, plays an important role in inflammation. The aim of this study is to investigate whether the early application of PCSK9 inhibitor can increase the myocardial salvage index (MSI) and improve ventricular remodeling in patients with STEMI. Design: The PERFECT II trial is a prospective, open-label, multicenter, randomized controlled study involving 160 patients with STEMI who are scheduled to undergo PPCI. The eligible patients will be divided into PCSK9 inhibitor group and control group via the interactive web response system, at a 1:1 ratio. In the PCSK9 inhibitor group, the PCSK9 inhibitor alirocumab at a dose of 75mg will be subcutaneously injected immediately after PPCI and administered every 2 weeks thereafter for 3 months based on conventional treatment. In the control group, conventional treatment will be administered. The primary endpoint is MSI, as measured by cardiac magnetic resonance imaging (CMR) at 1 week after PPCI. The secondary endpoints are the peak time of creatine kinase (CK)-MB and troponin I (TnI)/TnT after PPCI; the postoperative fall time of the ST segment on electrocardiography (ECG); the rate of plasma low-density lipoprotein cholesterol (LDL-C) compliance (<1.4mmol/L and a reduction of >50% from baseline) at 1, 3, and 6 months after PPCI; infarct size and ejection fraction (EF) measured by CMR at 6 months after PPCI; the occurrence of major adverse cardiovascular event (MACE: a composite of cardiovascular death, non-fatal myocardial infarction, stent thrombosis, repeat revascularization, stroke, and heart failure needed to be hospitalized). Conclusions: This is the first study to investigate the effect of early application of the PCSK9 inhibitor alirocumab on MSI in patients with STEMI undergoing PPCI. The findings will provide an opportunity to explore novel ideas and methods for the treatment of acute myocardial infarction. Trial registration: ClinicalTrials.gov, NCT05292404